A meta-analysis on verbal working memory in children and adolescents with ADHD. Issue 5 (3rd July 2020) - Ramos, Ari Alex; Hamdan, Amer Cavalheiro; Machado, Liana
Abstract: Objective: Previous meta-analyses have demonstrated verbal working memory (WM) dysfunction in children and adolescents with attention deficit/hyperactivity disorder (ADHD); however, the findings are inconsistent. The main objective of this meta-analysis was to investigate the performance of children and adolescents with ADHD in the Digit Span Backwards (DSB) subtest from the Wechsler Intelligence Scale for Children or Wechsler Adult Intelligence Scale. We also sought to provide an updated meta-analysis on WM in children and adolescents with ADHD. Method: PubMed, PsyINFO, Scopus, and Web of Science were searched to locate studies published between 1990 and 2016 that report DSB scores both of children and adolescents with ADHD and matched controls. Potential moderator variables were also analyzed. Results: Forty-nine studies comparing children and adolescents with ADHD ( n = 4956) against healthy controls ( n = 3249) generated a medium-sized effect (Hedges' g ) of 0.56 (95% CI [0.49, 0.64]), indicating poorer verbal WM performance in those with ADHD. A subgroup meta-analysis of studies with participants aged 8–16 years only demonstrated low heterogeneity ( I 2 = 17.06, cf. 55.50 for the main analysis). Moreover, the meta-regression showed a negative association ( β = –.05, p = .02) between DSB performance differences and increasing age, indicating that for every one year increase in age the effect size decreased by .05. Conclusion: These results, which emanated from the largest meta-analysis concerning verbal WM in ADHD reported to date, reinforce WM as a key domain of cognitive dysfunction in ADHD, and point to age as the main variable influencing DSB performance difficulties.